Kencur Supplementation Modulates Interleukin-6 (IL-6) and C-Reactive Protein (CRP) in Response to Muscle Damage Following Eccentric Exercise - Irawan, Roy Januardi; Roepajadi, Joesoef; Wahyudi, Heri; Kumaat, Noortje Anita; Tualeka, Abdul Rohim; Rimawati, Nanda; Wijayanto , Adi (Physical Education Theory and Methodology, 2025)
Background. Intense or unaccustomed exercise can cause muscle damage and tissue injury, leading to temporary muscle dysfunction and the release of pro-inflammatory cytokines and free radicals. These factors may result in muscle protein breakdown, impaired nutrient absorption, and hindered recovery. Objectives. This study aimed to evaluate the effects of Kencur supplementation on plasma IL-6 and CRP levels following eccentric exercise. Materials and methods. A randomized controlled trial (RCT) with a double-blind, placebo-controlled design was conducted with 40 male recreational students from the State University of Surabaya — Universitas Negeri Surabaya (age: 19.65 ± 1.09 years, BMI: 21.10 ± 1.16 kg, body fat percentage: 22.14 % ± 2.14 %). Participants were randomly assigned to either the Kencur group (200 mg/day) or the placebo group (corn starch 100 mg/day) for a period of 14 days. On the experimental day, participants performed 100 countermovement jumps (CMJ). Blood samples were collected immediately after, 24 hours, and 48 hours post-exercise to measure IL-6 and CRP levels. Repeated Measures ANOVA with Bonferroni Post-hoc tests were used to analyze the data. Results. The Kencur group showed a significant reduction in plasma IL-6 and CRP levels post-exercise at all time points (p < 0.05), while the placebo group exhibited no substantial changes (p > 0.05). Conclusions. The findings indicate that Kencur supplementation significantly reduces the inflammatory response by lowering IL-6 and CRP levels following eccentric exercise.